Variabilidade da condutividade hidráulica saturada da densidade aparente e da distribuição do tamanho das partículas de um podzólico vermelho-amarelo - Alves Pinto , Fernando; Afonso Ferreira , Paulo; Bernardo , Salassier; Maffia de Oliveira, Laede (Revista Ceres, 2025)
A study of soil water parameters variability was performed on a 4 hectare area within a uniform mapping unit at the Federal University of Viçosa. From 30 sites selected by a three-stage sampling design, 150 cores samples were collected at 20 cm depth intervals to 80 cm.